Chronic intermittent fasting impairs β cell maturation and function in adolescent mice - Matta, Leonardo; Weber, Peter; Erener, Suheda; Walth-Hummel, Alina; Hass, Daniela; Bühler, Lea; Klepac, Katarina; Szendrödi, Julia; Guerra, Joel; Rohm, Maria; Sterr, Michael; Lickert, Heiko; et al. (Cell reports, 2025)
Intermittent fasting (IF) is a nutritional lifestyle intervention with broad metabolic benefits, but whether the impact of IF depends on the individual’s age is unclear. Here, we investigated the effects of IF on systemic metabolism and β cell function in old, middle-aged, and young mice. Short-term IF improves glucose homeostasis across all age groups without altering islet function and morphology. In contrast, while chronic IF is beneficial for adult mice, it results in impaired β cell function in the young. Using single-cell RNA sequencing (scRNA-seq), we delineate that the β cell maturation and function scores are reduced in young mice. In human islets, a similar pattern is observed in type 1 (T1D), but not type 2 (T2D), diabetes, suggesting that the impact of chronic IF in adolescence is linked to the development of β cell dysfunction. Our study suggests considering the duration of IF in younger persons, as it may worsen rather than reduce diabetes outcomes.
Gesehen am 18.08.2025